Estudo da viabilidade da utilização de cinza de lodo de esgoto como adição em argamassa de cimento Portland - Costa, Felipe Murilo Silva da (2014)
The use of sewage sludge as a raw material falls within the waste recycling key in the current process model environmental sustainability .Waste recycling has been consolidated as a sustainable environmentally sound technical solution, and. Despite showing very variable composition and characteristics, sewage sludge, can be considered as a residue with a high recycling potential in the building sector. In this paper the feasibility of using sewage sludge ash was studied in addition to Portland cement mortar in 1:3 mass considered the standard dash. This gray additions were studied in proportions of 5%, 10 %, 15 %, 20 %, 25% and 30% by mass of cement. The methodology was focused on the characterization of materials by physical, chemical , mechanical , environmental and morphological followed by the production of mortar tests ,and finalized by the characterization tests of mortar in the fresh state, through the consistency index, content of entrained air, bulk density and water retention, and in the hardened state by bulk density, water absorption by capillarity capillarity coefficient, compressive strength, tensile strength in bending ,tensile bond strength and microstructural analysis for percentages of 0 to 20%. After comparing with the standard mortar mortars with addition of ash, it is concluded that the ash of sewage sludge did not impair the integrity and properties of mortars with addition, including increasing resistance to compression and tension, being 20% more indicated percentage. Thus, it becomes feasible the addition of sewage sludge ash in Portland cement mortar for the trait studied